Association Between Chromosome 4Q25 Polymorphism RS2200733 and the Incidence of Atrial Fibrillation in Bulgarian Patients - Dilyana Yakova-Hristova; Martin Hristov; Tihomir Rashev; Yoana Todorova; Pencho Tonchev; Nadya Stancheva-Hristova (Journal of Biomedical & Clinical Research)
Atrial fibrillation (AF) is the commonest type of arrhythmia seen in everyday clinical practice, which leads to a significant increase in both morbidity and mortality. Its incidence increases with age and tends to turn into an epidemic. The cause of AF in 10-20% of cases remains unknown. Several mutations and polymorphism that might be responsible for the development of AF have been found, including single nucleotide polymorphisms (SNPs) - rs2200733 and rs10033464 in the long arm of the fourth chromosome. These polymorphisms are selected o the basis of genome- wide association study in Iceland from 2007, the results from which were later confirmed in 4 other large populations. The rs2200733 is a common noncoding polymorphism, described in National Center for Biotechnology Information (NCBI) database dbSNP like NC_000004.12:g.110789013C>T, with a frequency of the less common allele between 0.1 and 0.24. In order to investigate the association between the rs2200733 polymorphism in chromosome 4q25 and the development of AF, we studied the frequency of this polymorphism in patients with heart diseases from the Pleven region, and thus evaluate the relationship between the individual genotype and the clinical condition of the patients. We carried out a case-control study on 80 patients: 40 with AF and 40 without AF- from the Pleven region. None of these had structural heart disease. The study was conducted between November 2015 and November 2017. With deoxyribonucleic acid (DNA) analysis, we determined rs2200733 polymorphism, using a TaqMan-based polymerase chain reaction (PCR). The Cochran-Armitage trend test, the Chi-Squared Pearson correlation, Fisher test we used confirmed the statistically significant association between the rs2200733 polymorphism in chromosome 4q25 and the development of AF. In the population examined, the genotypic frequencies were as follows: CC - 45 (56.2%), CT - 19 (23.8%), TT - 16 (20%), with value of Chi-Square (χ2) 24.496, df=2, p